2000
DOI: 10.1103/physreve.61.6294
|View full text |Cite
|
Sign up to set email alerts
|

Elastic moduli, dislocation core energy, and melting of hard disks in two dimensions

Abstract: Elastic moduli and dislocation core energy of the triangular solid of hard disks of diameter σ are obtained in the limit of vanishing dislocation-antidislocation pair density, from Monte Carlo simulations which incorporates a constraint, namely that all moves altering the local connectivity away from that of the ideal triangular lattice are rejected. In this limit, we show that the solid is stable against all other fluctuations at least upto densities as low as ρσ 2 = 0.88. Our system does not show any phase t… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

6
104
0

Year Published

2003
2003
2014
2014

Publication Types

Select...
7
2
1

Relationship

0
10

Authors

Journals

citations
Cited by 100 publications
(110 citation statements)
references
References 45 publications
6
104
0
Order By: Relevance
“…The investigation of melting in two dimensions still remains a very active research area, both experimentally (in colloids, [12][13][14][15][16][17] vortex flux lattices 18,19 and free-standing liquidcrystalline films 20 ) and numerically. [6][7][8][9][10][11][21][22][23][24][25][26][27] One reason the debate about the nature of the 2D melting transition is still continuing is that it is extremely difficult to distinguish between a weak, first-order melting transition and a continuous transition. The problem is that it is very hard to determine if the point where a solid becomes unstable toward dislocation unbinding is pre-empted by simple first-order melting.…”
Section: Introductionmentioning
confidence: 99%
“…The investigation of melting in two dimensions still remains a very active research area, both experimentally (in colloids, [12][13][14][15][16][17] vortex flux lattices 18,19 and free-standing liquidcrystalline films 20 ) and numerically. [6][7][8][9][10][11][21][22][23][24][25][26][27] One reason the debate about the nature of the 2D melting transition is still continuing is that it is extremely difficult to distinguish between a weak, first-order melting transition and a continuous transition. The problem is that it is very hard to determine if the point where a solid becomes unstable toward dislocation unbinding is pre-empted by simple first-order melting.…”
Section: Introductionmentioning
confidence: 99%
“…Hoogenboom and coworkers looked for an intermediate hexatic phase during crystallization at the flat bottom wall in a gravitational field, although its existence could not be verified due to polycrystallinity [25]. Earlier observations of the hexatic phase, in experiments [21,26 -28] and in simulations [29,30], have been made in thin confined systems and not at a single wall in a 3D system. Moreover, Fig.…”
mentioning
confidence: 99%
“…From the linear behaviour of a local order parameter they derived bounds for a possible coexistence region. Sengupta, Nielaba and Binder [16] simulated a dislocation free triangular solid of hard disks using a constrained Monte Carlo algorithm and showed that a KTHNY transition preempts a first-order transition. Combining renormalisation groups ideas with MC input they derived also an estimate of ρ m = 0.914(2) for a possible hexatic-to-crystal transition [17].…”
mentioning
confidence: 99%